Gaucher's Disease - A Case of Huge Hepatosplenomegaly Clinically Confused with Kala Azar: Case Report and Review of the Literature (Bangladesh Journal of Pathology, 2010)
Key words: Hepatosplenomegaly; kala azar; Gaucher's diseaseDOI: 10.3329/bjpath.v24i2.4115Bangladesh J Pathol 24(2): 25-33